Organic walled microfossils of the Barrandian area: A review - Fatka,O. (Journal of the Czech Geological Society, 1999)
The present contribution compiles all bibliographical references concerning Acritarcha, Prasinophyta, Mazuelloida, Chitinozoa, Spores, and Cyanobacteria described in the Proterozoic, Cambrian, Ordovician, Silurian, and Devonian sediments of the Barrandian area. More than 130 references include books, publications in journals, abstracts from international and national conferences. The survey of literature resulted into compilation of five tables where separate papers dealing with the above mentioned groups are graphically related to the studied stratigraphical intervals.
Keywords: Bohemia; Barrandian area; Proterozoic; Cambrian; Ordovician; Silurian; Devonian; organic-walled microfossils